Sustainable Tourism Development in Indonesia: A Critical Evaluation of Economic Philosophy - Dede Rusmana; Heri Pratikto; Agung Winarno (Enigma in Economics, 2025)
Sustainable tourism has emerged as a paradigm for reconciling the economic benefits of tourism with the need to protect the environment and preserve cultural heritage. This study was aimed to evaluate the economic philosophies underpinning sustainable tourism development in Indonesia. This research employed a qualitative research methodology. Data was collected through a comprehensive literature review encompassing academic journals, books, government reports, and non-governmental organization (NGO) publications. The collected data was then analyzed using thematic analysis to identify key themes and patterns related to economic philosophies and sustainable tourism practices in Indonesia. The findings reveal a dominant focus on neoliberal economic principles in Indonesian tourism, prioritizing economic growth and foreign investment. However, this approach has led to several negative consequences, including environmental degradation, social inequalities, and cultural commodification. Alternative economic philosophies, such as community-based tourism and degrowth, offer more sustainable and equitable pathways for tourism development. In conclusion, a paradigm shift is necessary to achieve sustainable tourism development in Indonesia. Moving away from a purely neoliberal framework and embracing alternative economic models that prioritize community well-being, environmental protection, and cultural preservation is crucial. This shift requires a collaborative effort from government, industry, and local communities.